İngilizce Öğretmenliği Alanında 21. Yüzyıl Becerileri Üzerine Yapılmış Çalışmaların Bibliyometrik Çalışması - Özçelik, Nermin Punar; Uka, Ecem Eker (Fırat University, 2023)
The more the era has been changing, the more the skills we need have been changing, as well. Living in such a new era brings along the requirement for new skills. 21st-century skills are the skills that we exactly need nowadays as researchers, students, executives, etc. Due to globalization and digitalization, the research focus on 21st-century skills has been increasing day by day, and it is important for researchers to know the gaps in the field and the topics being researched so that they can focus on the gaps and have the possibility to study more to fill those gaps. Grounded on this, the present study aims to find out the most searched topics/keywords, the most cited authors, and the most productive countries on the topic of 21st-century skills in the field of English language teaching, by conducting a bibliometric research study. The results showed that most of the studies focused on creativity, collaboration, communication, and critical thinking, with scant attention to life and career skills while giving an increasing interest in digital literacy skills.

The more the era has been changing, the more the skills we need have been changing, as well. Living in such a new era brings along the requirement for new skills. 21st-century skills are the skills that we exactly need nowadays as researchers, students, executives, etc. Due to globalization and digitalization, the research focus on 21st-century skills has been increasing day by day, and it is important for researchers to know the gaps in the field and the topics being researched so that they can focus on the gaps and have the possibility to study more to fill those gaps. Grounded on this, the present study aims to find out the most searched topics/keywords, the most cited authors, and the most productive countries on the topic of 21st-century skills in the field of English language teaching, by conducting a bibliometric research study. The results showed that most of the studies focused on creativity, collaboration, communication, and critical thinking, with scant attention to life and career skills while giving an increasing interest in digital literacy skills.
A Bibliometric Analysis of the Studies on 21st-century Skills in ELT
Keywords: Other Fields of Education; Alan Eğitimleri